2016
DOI: 10.4102/sajems.v19i4.1404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the South African input-output table to determine sector specific economic impacts: A study on real estate

Abstract: Input-output analysis is a well known method of analysing specific economic activity and the influence of different sectors on the economy and on one another. This study investigates the ability of input-output analysis to consider the importance of commercial real estate on the economy. It analyses the economic activity, contribution to GDP, employment created and taxes generated with reference to direct, indirect and induced impacts. The research shows the contribution of the specific sector on the economy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In its simplest expression, a green economy can be thought of as one which is low carbon, resource efficient and socially inclusive. (p. 9) http://www.sajems.org Open Access (Majory & Stephen 2011; Van Seventer 1999), on using inputoutput methods (Boshoff & Seymore 2016;Kavese & Phiri 2020;Park & Chan 1989), on utilising Bayesian methods (Kim & Hewings 2019), or on combining input-output analysis and system dynamics modelling (Uehara, Cordier & Hamaide 2018). In this paper, all these elements are combined in order to forecast not only national gross value added (GVA), but also provincial GVA, and estimate the relevant provincial multipliers.…”
Section: Introductionmentioning
confidence: 99%
“…In its simplest expression, a green economy can be thought of as one which is low carbon, resource efficient and socially inclusive. (p. 9) http://www.sajems.org Open Access (Majory & Stephen 2011; Van Seventer 1999), on using inputoutput methods (Boshoff & Seymore 2016;Kavese & Phiri 2020;Park & Chan 1989), on utilising Bayesian methods (Kim & Hewings 2019), or on combining input-output analysis and system dynamics modelling (Uehara, Cordier & Hamaide 2018). In this paper, all these elements are combined in order to forecast not only national gross value added (GVA), but also provincial GVA, and estimate the relevant provincial multipliers.…”
Section: Introductionmentioning
confidence: 99%
“…Our study not only aims to fill this identified gap by providing forward and backward tax multipliers for the South African economy, but we further address other gaps identified in the literature. For instance, previous studies that applied Leontief-based multiplier models to the South African economy, generally focused either on one sector, for example the mining sector (Stillwell 1999), real estate (Boshoff & Seymore 2016), sugar-sweetened beverages (National Treasury 2017), or the agricultural sector (Phoofolo 2018), or their analysis was static, based on a single year (Cloete & Rossouw 2014;Davies & Thurlow 2013;Van Seventer et al 2016). Kratena and Streicher (2017) used the traditional IO, a static model, to analyse fiscal policy multipliers and spillovers in a multi-regional macroeconomy.…”
Section: Introductionmentioning
confidence: 99%